Europe - quo vadis? Reflections on the future institutional framework of the European Union - Horst Siebert (Kiel Institute of World Economics (IfW), 2001)
With twelve new members the decision making in the European Union via intergovernmental cooperation will become ineffective. In order to avoid a Stagno-Europe the EU has a choice: Either it looks for the very essentials in the common institutional frame or the member states agree in ceding national sovereignty to the European level. This, however, requires that the democratic deficit at the EU level is reduced. The Treaty of Nice has failed to solve these issues.
Keywords: F15; F00; D70; 330; enlargement; european integration; Europäische Integration; EU-Erweiterung; Public Choice; Wirtschaftsunion; Verfassungsreform; EU-Staaten